Role of laparoscopy in treatment of tubercular pyoperitoneum - Goel, Anubhav; Bansal, Ankur; Rana, Jinendra; Kumar, Chandrodaya (International Surgery Journal, 2018)
Background: Abdominal TB, which may involve the gastrointestinal tract, peritoneum, lymph nodes or solid viscera, constitutes up to 12% of extrapulmonary TB and 1-3% of the total. Tuberculosis can involve any part of the gastrointestinal tract and is the sixth most frequent site of extrapulmonary involvement. Both the incidence and severity of abdominal tuberculosis are expected to increase with increasing incidence of HIV infection. Peritoneal tuberculosis occurs in three forms: wet type with ascitis, dry type with adhesions, and fibrotic type with omental thickening and loculated ascites. Aim of the present study was to evaluate the role of laparoscopy in cases of pyoperitoneum. Methods: In present study authors included the cases of pyoperitoneum which is diagnosed by ultrasound aspiration and no sign of perforation of bowel and is hemodynamic stable. Results: A total of 14 cases of pyoperitoneum were included. All underwent diagnostic laparoscopy. 3 had underlying ruptured appendicitis and excluded from study. Rest 11 had no perforation associated with it. 7 were female and 4 were male. Through lavarge of peritoneum done and drain placed in pelvis. Fluid was sent for ADA estimation which was increased in all eleven cases. DOTS treatment was started in all cases and they respond well to treatment in 6 month follow up. Conclusions: Tubercular pyoperitoneum is common entity in surgical setting. Laparoscopy has got encouraging role in these cases as it avoids laparotomy and complications associated with it.